2015
DOI: 10.1016/j.jpsychires.2015.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Brain and behavioral evidence for altered social learning mechanisms among women with assault-related posttraumatic stress disorder

Abstract: Current neurocircuitry models of PTSD focus on the neural mechanisms that mediate hypervigilance for threat and fear inhibition/extinction learning. Less focus has been directed towards explaining social deficits and heightened risk of revictimization observed among individuals with PTSD related to physical or sexual assault. The purpose of the present study was to foster more comprehensive theoretical models of PTSD by testing the hypothesis that assault-related PTSD is associated with behavioral impairments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…Middle frontal gyrus is crucial for executive control, working memory and emotion processing that are disrupted in PTSD (Morey et al, 2009). A previous task-based fMRI study also showed that PTSD patients demonstrated disrupted responses to trauma stimuli in bilateral middle frontal cortex (Hou et al, 2007), and it has been speculated that heightened encoding of negative expected social value in middle frontal gyrus might contribute to hypervigilance and attentional biases for threat in PTSD patients (Cisler et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Middle frontal gyrus is crucial for executive control, working memory and emotion processing that are disrupted in PTSD (Morey et al, 2009). A previous task-based fMRI study also showed that PTSD patients demonstrated disrupted responses to trauma stimuli in bilateral middle frontal cortex (Hou et al, 2007), and it has been speculated that heightened encoding of negative expected social value in middle frontal gyrus might contribute to hypervigilance and attentional biases for threat in PTSD patients (Cisler et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Our data accompany several others that have found effects for trauma and PTSD on social function. For instance, women with PTSD have altered social learning that may predispose them to re-victimization (Cisler et al, 2015). Trauma survivors with PTSD exhibit lower empathic resonance (Nietlisbach, Maercker, Rossler, & Haker, 2010), and have deficits in mentalizing and emotion recognition (Plana, Lavoie, Battaglia, & Achim, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The authors also examined this same sample in a related paradigm that attempted to address the social deficit symptomatology observed to be characteristic of PTSD ( Cisler et al, 2015 ). Specifically, the authors utilized a behavioral Trust Game completed outside the scanner in which participants invested a chosen amount of money into another “player” on each trial (which was, unbeknownst to them, actually a computer), and could receive back a portion of the tripled investment dictated by the other player on each trial.…”
Section: Reward Circuit Function and Behavior In Ptsdmentioning
confidence: 99%
“…Initial efforts in PTSD to utilize theory-driven computational models to infer latent parameters of information processing involved in reward-based decision making have already surfaced ( Myers et al, 2013 ), including the integration of these models with imaging data to bridge behavioral and brain-based units of analysis ( Cisler et al, 2015 ; Ross et al, 2018 ). Such an approach holds tremendous value for advancing the field of biological psychiatry more generally ( Montague et al, 2012 ; Wang and Krystal, 2014 ) but also for PTSD and trauma affective neuroscience research more specifically for several reasons.…”
Section: Future Directions In Trauma Affective Neuroscience Research:mentioning
confidence: 99%